Creativity and innovation in achieving success in traditional cake businesses - Shofia Amin; Indra Jaya (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Many factors influence the success of a business, either internal or external factors. This study aims to examine the interrelationship of internal factors in the form of creativity and innovation to the success of the businesses of traditional cake. Using quantitative methods, data was collected through questionnaires to 37 traditional cake entrepreneurs in Kuala Tungkal City, Tanjung Jabung Barat Regency, Jambi Province. Analysis was done by using path analysis. The results show that creativity and innovation both simultaneously and partially have a positive effect on the success of traditional cake businesses. Innovation has more dominant influence than creativity in the success of businesses. From the descriptive analysis it was found that the success of the business in the form of increasing income was not followed by the addition of new customers. Therefore it is recommended for the entrepreneurs to innovate in product, process, place and design to be able to attract new customers.